A Highly Efficient Palladium‐Catalyzed Decarboxylative ortho‐Acylation of Azobenzenes with α‐Oxocarboxylic Acids: Direct Access to Acylated Azo Compounds. Issue 43 (23rd September 2013) - Li, Hongji; Li, Pinhua; Tan, Hui; Wang, Lei
<x xml:space="preserve">Abstract</x> Avoiding additives: A highly efficient and mild Pd‐catalyzed decarboxylative ortho‐acylation of azobenzenes with α‐oxocarboxylic acids was developed that provides an alternative route to acylated azo compounds. This decarboxylative acylation process was completed in the absence of any additives at ambient temperature, to afford the acylated azobenzenes in moderate to good yields (see scheme).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>